RELIGION AND CULTURE BASED ARTS SUSTAINABILITY MODEL IN THE “AMONG” SYSTEM: EMPIRICAL STUDY IN BUTUH, THE WAYANG HAMLET - Kusumawati, Ita Rahmania (ISI Press Institut Seni Indonesia Surakarta, 2024)
It is scarce to find a village where most of its citizens are engaged in traditional wayang crafts, especially if the most residents are Muslims. Moreover, the number of puppets needed to fulfill shadow puppet shows is limited throughout the world. However, the fact shows that Butuh Hamlet has a majority of residents who work as wayang artisans and still exist today, a model for the continuation of traditional arts in facing tough challenges and is an example of the sustainability of traditional arts in facing tough challenges, both externally and internally. This sustainability can be seen in the number of residents who still pursuing the crafting profession, which craft are still the main source of income for residents. Butuh Hamlet has received the title of Kampung Berseri (a beautiful and clean village). Apart from that, they also continue to work on strengthening the wayang craft with the Among System: caring for, fostering, and sharpening each other in developing the wayang craft. The sustainability of wayang as a means of livelihood and a medium for preaching (da'wah) has made the lives of artisans better.